Effectiveness of Tongguan capsules on restenosis after coronary stent implantation: a randomised controlled trial. (December 2017) - Zhang, Minzhou; Guo, Liheng; Zhou, Yuanshen; Mao, Shuai
Abstract: Background: Although percutaneous coronary intervention (PCI) has become a widely used therapeutic procedure for coronary artery disease, stent restenosis limits the benefits of this revascularisation. The question of how to prevent such events remains unresolved. Empirical evidence suggests that Tongguan capsules, a patented Chinese Medicine, can decrease frequency and duration of angina pectoris attacks; however, evidence supporting its efficacy on restenosis remains inadequate. We aimed to determine whether Tongguan capsules could reduce restenosis incidence in patients after successful stent implantation. Methods: In this single-centre, open-label randomised controlled trial, patients undergoing percutaneous coronary stent deployment who were aged 18–80 years were enrolled from Guangdong Provincial Hospital of Chinese Medicine and randomly assigned (1:1) to receive either Tongguan capsules for 3 months (4·5 g/day; Tongguan group) or nothing (control group). All patients received standard anti-platelet, anti-coagulation, and lipid-decreasing treatments, concurrently. The Clinical Research Centre from Guangzhou University of Chinese Medicine generated separate randomisation schedules using a random number generator. All attending physicians, investigators, and the biostatisticians performing the analysis were masked to treatment assignment. The primary clinical endpoint was the 12-month incidence of any major adverse cardiovascular event (defined as cardiac death, myocardial infarction, or recurrence of symptoms requiring additional revascularisation). The primary angiographic endpoint was restenosis incidence at 6 months. The Clinical Research Ethical Committee at Guangdong Provincial Hospital of Chinese Medicine approved the research protocol (Z2017008-01). This trial was registered in ChiCTR (ChiCTR-IIR-17011407). All participants provided written informed consent before enrolment. Findings: We enrolled 326 patients between Aug 1, 2014, and Dec 1, 2015. Of these patients, 163 were randomly assigned to the Tongguan group and 163 to the control group. Four patients were excluded leaving 322 patients (160 in the Tongguan group and 162 in the control group) for analysis. Compared with the control group, 12-month incidence of major adverse cardiovascular events was reduced in patients treated with Tongguan capsules (12·5% [20 of 160] vs 23·5% [38 of 162], p<0·0001); 6-month restenosis incidence did not differ between groups (3·1% [five of 160] in the Tongguan group vs 4·3% [seven of 162] in the control group, p=0·779). Interpretation: Although not significant, there was a trend towards a reduction in restenosis and therefore more research is needed to establish whether Tongguan capsules can improve clinical outcomes. Further higher quality and more rigorous randomised trials with larger sample size are needed to attain more robust clinical evidences of Tongguan capsules. Funding: National Science Foundation (81473471, 81202782, 81573708).